Active learning using PBL and DELMAN method to enhance students’ Higher Order Thinking Skills (HOTS) on Coulomb’s Law material - Kurniawan, Aris; Kuswanto, Heru; Syar, Nur Inayah (Momentum: Physics Education Journal, 2025)
This study aimed to investigate: (1) the enhancement of students' HOTS, and (2) the effectiveness of the Problem Based Learning (PBL) model combined with the DELMAN method in enhancing students' HOTS in the context of Coulomb's Law. This study employed a quasi-experimental design utilizing a non-equivalent control group. The participants consisted of two classes of Grade 12 students: one class of Science 2 students as the experimental group, while a class of Science 1 students as the control group. A HOTS test consisting of 12 multiple-choice questions was used as the research instrument. Data analysis was conducted using N-Gain scores and General Linear Model (GLM). The findings showed a notable difference in the improvement of HOTS between the experimental and control groups, with a significance level of <0.05. The experimental group, which utilized the PBL model combined with the DELMAN method, achieved a gain score classified as moderate, while the effect size was considered very large. These findings suggest that the PBL model combined with the DELMAN method is effective in enhancing the HOTS of high school students.